(untitled) (Journal of Geography and Environmental Management, 2018)
In this article considered and systematized to the feature of the given services in accordance by demand of consumers on the enterprises of public food consumption.With this цельюпровели marketing researches by the method of questionnaire in area of satisfactions of necessities of consumers by quality of the rendered services and of long duration relations between restaurants and guests. Except it, description of personnel of restaurant was created, on the basis of psychological aspects, such as, communication of employees inter se and by a guest. On the basis of to research work, using the method of questionnaire, by authors on the example of restaurant of “Тaу Дaстaрхaн” was certain level of satisfaction of the Kazakhstan consumers. In a percent index, recommendations were similarly given for улучению qualities of окозaния services in restaurants.